ENCODING AGRICULTURAL DISCOURSE IN THE CONSTRUCTION OF AGRARIAN LITERACY OF FARMERS IN THE MASS MEDIA - Wahyuni, Lilik; Islahuddin, Islahuddin (Jurnal Penelitian Humaniora, 2023)
Agricultural discourse is the result of conveying a message to increase the agrarian literacy of a community to become agriculturally literate. The goal of this research is to obtain an objective picture about the text structures, social cognition, and social contexts used in the construction of agricultural discourse to establish the agrarian literacy of farmers. The research uses a qualitative method with a symbolic interactionism design to study the way a social interaction is constructed and developed. The data collection methods used were documentation and a content review. The data sources for the research were newspapers and YouTube. The data analysis used a descriptive qualitative method with the stages of identification, classification, and interpretation. The results of the research show that (1) the text structures used to establish agrarian literacy include elements of semantics and syntax, (2) the forms of social cognition utilized by speakers to shape the discourse are person schemes, role schemes, and event schemes, and (3) the social contexts that influence speakers in carrying out encoding are food security and sovereignty, agricultural consultants, and millennial farmers.